Efficacy of glycolic acid on debris and smear removal as a final rinse solution in curved canals: A scanning electron microscope study - Karunakaran Jeyaraman Venkataraman; Suresh Krishna Boominathan; Ragavendran Nagappan; Chris Susan Abraham; Anbarasi Kaliyaperumal; Jayaprakash Nachimuthu; Modachur Muruganathan Premkumar (Wolters Kluwer Medknow Publications, 2021)
Aim: This study aims to compare intraradicular smear layer removal efficacy of different concentrations of glycolic acid (GA), 17% ethylenediaminetetraacetic acid (EDTA), and 10% citric acid (CA) as final rinses in the canals of curved mesial root of mandibular first molars using the specific irrigant protocols. Materials and Methods: Fifty-eight mandibular first permanent molars with 15°-30° of curvature of the mesial roots were selected, standardized, mesiobuccal canal prepared using the rotary instrumentation. Sodium hypochlorite was used as initial rinse solution (8 ml). The samples were divided into control (n = 5) (I - Normal saline and II - 17% EDTA) and experimental groups (n = 8) (Groups III, IV, V, VI, VII, and VIII) based on the type of final rinse solution (5 ml) used, i.e. 2.5% GA, 5% GA, 10% GA, 17% GA, 37% GA, and 10% CA. Samples were split buccolingually, dehydrated, splutter coated, and examined under a scanning electron microscope. Results: Group IV presented the least amounts of smear among the GA experimental groups at the apical, middle, and coronal one-thirds of the root canal with a mean value of 2.6 ± 1.012, and on comparison with Group II, the results were comparable, and no significant difference found statistically (P > 0.05). Conclusion: The use of GA as final rinse solution for biomechanical preparation during endodontic therapy seems promising. Further evaluation in a clinical setting is recommended.